Integrated service post information system to support baby growth data reporting - Syaidaturrahmi (Politeknik Ganesha Medan, 2022)
The manifestation of technological advances that have played a role in various fields is information systems. Information systems are widely applied in various government agencies such as aspects of education, economy and health. The government seeks to improve services in the health sector by carrying out community empowerment activities through Integrated Service Posts. In its implementation, the Integrated Service Post still uses the manual method, namely recording participant data from the Integrated Service Post, data on measuring baby's height and weighing baby's weight, vitamins and immunizations as well as the results of health checks for pregnant women and the elderly. Considering that continuous monitoring of infant growth and development is very important, the manual system becomes less effective. Thus, the existence of an Integrated Service Post information system helps data collection on infant growth and development as well as the health status of pregnant women and the elderly to be more effective. Researchers used research methods in the form of observation, interviews and literature study. The system design uses Unified Modeling Language and its development uses Rapid Application Development. The results of this study are a website-based Integrated Service Post information system for the implementation of Integrated Service Posts.